I know a place : rest stop and other dark detours - Cassidy, Nat, 1981- (Shortwave Publishing, 2026)
"There are locations in this world where the light doesn't seem to reach. Where, no matter how illuminated the place might be, shadows creep in too strongly to fight back. A suspiciously empty gas station rest stop in the middle of the night, littered with googley eyes... A doctor's office, where a bottle of booze and a tear-stained folder wait on the desk... A tech millionaire's haunted kitchen... A Bible-quoting ventriloquist's dingy apartment... A yoga retreat in the middle of the desert, silent except for the screaming... These locations and more are your destination and bestselling author Nat Cassidy will be your guide. Featuring the Bram Stoker Award-nominated, critically acclaimed novella Rest Stop (one of Esquire's Best Horror Books of 2024), along with a number of other original short stories, some which have never been published before, I Know A Place: Rest Stop and Other Dark Detours is a travelogue down twisting side streets and through alleyways where the darkness has eyes... and teeth. Let's hope you make it home in one piece."--